Hemangioblastoma in the lateral ventricle: An extremely rare case report - Pan, Ruihan; Shi, Jianwei; Xu, Yang; Bo, Fuduo; Luo, Zhengxiang; Zhang, Yansong (Frontiers in Oncology, 2022)
Hemangioblastoma (HB) is a benign vascular tumor that accounts for approximately 2% of intracranial neoplasms. HB of the lateral ventricles is extremely rare. Only a few reports are present in the literature. This article reports a 27-year-old male patient who arrived at our hospital because of a progressive headache lasting one month. The brain Magnetic Resonance Imaging (MRI) revealed a solid-cystic mass of 3.5×3.0 cm in size located in the left lateral ventricle, the surgery was performed by applying an interhemispheric approach to single frontal craniotomy with coronal incision to remove the tumor. The postoperative CT and MRI showed the successful complete removal of the tumor and a normal ventricle morphology. The differential diagnosis should be considered in case of intraventricular tumors including HB. Angiography should be performed prior to surgery when HB is suspected.